ICT FOR LEARNING AND TEACHING ENGLISH - Santy Christinawati; Wahyu Trimastuti (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
This study aims to analyze ICT use in learning and teaching English. The purpose of this study was to find the effectiveness of ICT usage in learning and teaching English easier and more fun. ICT drives towards greater use of technology in education is changing at modernizing polytechnic and equipping the students of today with skills that will make them able to use such technology. Other state goals have been to reduce lecturer work-load by making planning and resources available over the internet. This study focuses on: (1). What are advantages and disadvantages that ICT can have positive impact on students’ learning in English language? (2). Can ICT help the lecturers and students give better ambience for learning process? (3). What are tools of technologies that can be used in learning and teaching English? The data for this study was taken from the students in Health department especially Medical Records class. The implementation of such technologies for learning and teaching English can encourage students to become more independent and more responsible for their learning process in education environments.